Transforming Supplier Audits with AI: A Risk-Based Approach in Medical Devices (International Journal of Scientific Research and Management (IJSRM), 2024)
The medical device industry, highly regulated and sensitive to quality standards, relies on rigorous supplier audits to ensure compliance and mitigate risks. However, traditional supplier audits are often resource-intensive, inconsistent in quality, and lack a clear focus on the most critical risk factors. This paper explores how Artificial Intelligence (AI) can revolutionize the supplier audit process by enabling a risk-based approach that enhances accuracy, efficiency, and regulatory compliance. AI technology, with its advanced data processing, predictive analytics, and machine learning capabilities, can analyze vast amounts of supplier data in real-time, generating risk scores that prioritize high-risk suppliers for more frequent and thorough audits. This shift allows medical device companies to better allocate resources, focusing on high-impact areas and enhancing overall supply chain security. By considering factors such as supplier compliance history, product criticality, regional compliance laws, and performance trends, AI provides a dynamic and data-driven assessment model that minimizes the reliance on subjective audit practices. The paper introduces an AI-powered risk-based audit framework specifically tailored for medical device companies. This framework utilizes a multi-faceted AI-driven risk scorecard, categorizing suppliers by risk levels (high, medium, low) and enabling targeted audit strategies. It also demonstrates how AI can process a wide array of audit-related data inputs—such as supplier compliance, regional geopolitical risks, supply volume, and product criticality—to generate a holistic and accurate risk assessment. Through case studies and industry examples, this research underscores the advantages of integrating AI into supplier audit processes, highlighting cost savings, improved compliance outcomes, and reduced risk of quality issues or product recalls. Furthermore, it examines future trends and ethical considerations of AI in supplier audits, advocating for industry-wide adoption of AI-powered tools to support more efficient and effective supplier management. This paper concludes that adopting a risk-based, AI-driven audit approach in the medical device sector not only supports regulatory compliance but also builds resilience within the supply chain, creating a safer and more efficient landscape for medical device production.